2016
DOI: 10.1007/s13205-016-0562-z
|View full text |Cite
|
Sign up to set email alerts
|

Brevibacillus borstelensis and Streptomyces albogriseolus have roles to play in degradation of herbicide, sulfosulfuron

Abstract: Use of herbicides, in particular sulfosulfuron, at more than recommended doses has raised major concerns about the health hazards for animals and humans. In the present study, isolation of sulfosulfuron-degrading Brevibacillus borstelensis and Streptomyces albogriseolus from the field soils in the northwestern region of India was carried out where the use of sulfosulfuron is predominant, and further assessed for their potential to degrade sulfosulfuron individually and together in a consortium form under lab c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Brevibacillus borstelensis is a thermophilic bacteria and was isolated from Kalajoha with a similarity of 100%. It was found previously in, ’Marcha’- a herbal cake used as traditional starter culture to ferment local wine in north-east India and rhizosphere of wheat from northern region of India [25, 26]. But it has not been earlier reported as an endophyte of rice.…”
Section: Discussionmentioning
confidence: 99%
“…Brevibacillus borstelensis is a thermophilic bacteria and was isolated from Kalajoha with a similarity of 100%. It was found previously in, ’Marcha’- a herbal cake used as traditional starter culture to ferment local wine in north-east India and rhizosphere of wheat from northern region of India [25, 26]. But it has not been earlier reported as an endophyte of rice.…”
Section: Discussionmentioning
confidence: 99%
“…The soils used for this study have similar pH levels (7.6 to 7.8) at which chemical hydrolysis is slow and degradation is largely due to microbial breakdown (Beyer et al 1988). Recent studies reported on the isolation of different sulfosulfuron-degrading microorganisms (Arya et al 2016; Yadav and Choudhury 2014). It is thus most likely that differences in the biodegradation rate of sulfosulfuron are the cause for varied degradation rates and residual activity recorded in the current study (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Some research in relation to the co-culture was also conducted on Streptomyces albogriseolus with Brevibacillus borstelensis from the eld soils in the northwestern region of India. The Actinobacteria was managed to reduce the concentration of sulfosulfuron from 10 g/ml in an initial hour from 8.34 g/ml in 12 h to 6.66 g/ml in 20 h (Arya et al 2016). However, there has been no research on co-culture with Streptomyces albogriseolus as an antibacterial.…”
Section: Discussionmentioning
confidence: 99%